Atraumatic Restorative Treatment in permanent molars: a systematic review - Liana Studart; Carolina da Franca; Viviane Colares (Universidade Estadual de Campinas, 2015)
Aim: This paper presents a systematic review of studies published within the last 10 years on Atraumatic Restorative Treatment (ART) in permanent molars. Methods: A systematic search was carried out in the MEDLINE and PubMed databases from April 1st 2001 to December 31st 2010 using the term "atraumatic restorative treatment" and in the LILACS database using the term "tratamento restaurador atraumático". The selection of publications was based on the following criteria: texts written in English, Spanish or Portuguese; presence of an abstract; and investigation of clinical aspects related to ART in permanent molars. Results: The analysis of abstracts led to the selection of 26 studies. Recent clinical studies on ART in permanent molars of children, adolescents and young adults mainly address the survival of restorations through a comparison between caries removal methods and restorative materials. The publications report a survival success rate of ART restorations ranging from 30 to 100% in permanent molars, which is similar to that reported for treatments employing conventional methods and materials. The success rate of ART sealants ranged from 6.2 to 98.5%. The number of studies reporting on the retention and caries preventive effect of ART sealants was small. Conclusions: This systematic review revealed high survival rates for single-surface ART restorations in permanent molars and lower success rates for multiple-surface restorations. Clinical studies conducted with children, adolescents and young adults demonstrate a reliable clinical performance of single-surface and multi-surface ART restorations for 3-year and 2-year periods, respectively. However, long-term clinical studies are scarce and most of them focus on one-surface cavities. The survival rates observed, especially for single-surface restorations, confirm the potential of the ART approach for restoring and saving permanent molars. More clinical studies are required on the retention and caries preventive effect of ART sealants.